IMPACT OF INTERNAL AUDIT ON CORPORATE FINANCIAL INDICATORS - Prokopchuk, L.M. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Specific features of the Ukrainian economy contribute to the rethinking of global and domestic experience of internal audit and its practical implementation in the corporate governance system in order to improve the financial performance of corporations. The study is based on an analysis of the impact of internal audit on the financial KPI of the corporation. It is established that today, in the light of modern rule-making processes in our country, it is critical to understand the importance and essence of the function of internal audit and its potential in improving the quality of financial reporting. The article offers a method of analysis of the main factors of the effectiveness of carry through of internal audit at the leading enterprises of Ukraine. The result of the developed methodology is the study of the influence of selected factors, which allowed to establish that the key conditions for the effective impact of internal audit on the financial performance of the corporation are high professionalism of internal auditors and organized audit service..